Cognitive Biases and the Cultural Disconnect between Engineers and Decision-makers - Booker, Nigel; Gates, Jeffrey D.; Knights, Peter (Technium Social Sciences Journal, 2021)
Engineering culture is alien to the way the average person thinks and makes decisions. There is a dichotomy between the evidence-based analytical methodologies used by engineers and the intuitive or heuristic processes commonly used by the general public. Both can be appropriate in context, but wrong choices can lead to undesirable and sometimes dire consequences. For the recommendations from an engineering analysis to be accepted by non-technical decision-makers, the findings must be presented in a manner that takes account of human factors. Successful engineers are those who are proficient in translating the language of their technical discipline into that of broader society. A key skill is consequential reasoning, which is contained within engineering codes of ethics but is also critical to the persuasive power of analytical findings. Students and early-career engineers need structured learning in communication and in socio-cultural and emotional intelligence. They need exposure to cognitive psychology and epistemology, especially in relation to bias and false logic. If formal humanities courses cannot be accommodated in the undergraduate engineering degree, then post-graduate and continuing professional development opportunities should be offered.